Model rachunku kosztów docelowych zorientowanego na kreowanie wartości - Masztalerz, Marek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents the key elements of the Value-Based Target Costing (VBTC) model built by the author in his theoretical research. The VBTC model links the target costing method and the value creation concept. Two different value-oriented target cost calculation models are built. The first model is based on the free cash flow approach (NPV & IRR) and the second - on the residual income approach (EVA & MVA). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 220-229